INTERNATIONALIZATION OF TRANSFORMATIVE ISLAMIC EDUCATION: MOESLIM ABDURRAHMAN, TRANSFORMATIVE ISLAM AND MUHAMMADIYAH - Khoirudin, Azaki; Eka Saputra, Sawaluddin (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2018)
This thesis examines the institutionalization of the transformative Islamic idea of Moeslim Abdurrahman in the field of Islamic education. by proposing the problem: How to construct Moeslim Abdurrahman?s transformative Islam and the thinking and to institutionalization of transformative Islam Moeslim Abdurrahman, Theis present study research is library research, hence all of this research activity is focused on studying books and literature that have relevance to the subject. Furthermore, This study uses a hermeneutic approach that is used to that is boldly and objectively interpreted frankly and objectively might be a symbol in the form of text in order to get a profound true understanding. The method of data analysis used is descriptive-analytic method, which that is to description regularly and meticulously analyze as carefully as possible, the data related to the idea of Moeslim Abdurrahman?s about transformative Islamic education by describing the points thoroughly, then analyzed and. Subsequently, then the author tries to give an interpretation of the idea thinking of the figure reviewed. The result of this research shows is the construction of transformative Islamic thought of Moeslim Abdurrahman departing from the transformative theology of reviving the message of God in religion ( in Islam) to predispose side by side the marginal, and at the same time, to the theology has revitalizeenlivened the spirit of transformative pedagogy (critical learning) with the influence of political mechanism by involving the community to interpret it critically., Furthermore, and the institutionalization of the idea of Islam transformative Islam (Knowledge) of Moeslim Abdurrahman (Person) in Islamic education (JIMM) is done through externalization, that later then experiencing objectification among the young Muhammadiyah youth children through after an the internalization process.